Influence of dielectric materials on uniformity of large-area capacitively coupled plasmas for N2/Ar discharges - 梁英爽 张钰如 王友年 (中国物理B：英文版, 2016)
The effect of the dielectric ring on the plasma radial uniformity is numerically investigated in the practical 450-mm capacitively coupled plasma reactor by a two-dimensional self-consistent fluid model. The simulations were performed for N2/Ar discharges at the pressure of 300 Pa, and the frequency of 13.56 MHz. In the practical plasma treatment process,the wafer is always surrounded by a dielectric ring, which is less studied. In this paper, the plasma characteristics are systematically investigated by changing the properties of the dielectric ring, i.e., the relative permittivity, the thickness and the length. The results indicate that the plasma parameters strongly depend on the properties of the dielectric ring. As the ratio of the thickness to the relative permittivity of the dielectric ring increases, the electric field at the wafer edge becomes weaker due to the stronger surface charging effect. This gives rise to the lower N2+ ion density, flux and N atom density at the wafer edge. Thus the homogeneous plasma density is obtained by selecting optimal dielectric ring relative permittivity and thickness. In addition, we also find that the length of the dielectric ring should be as short as possible to avoid the discontinuity of the dielectric materials, and thus obtain the large area uniform plasma.